Obstetrics and Gynaecology in Tudor and Stuart England - Eccles, Audrey; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
Originally published in 1982 Obstetrics and Gynaecology in Tudor and Stuart England traces the development of obstetrics and gynaecology over the past two centuries. Between the 16th and 18th century midwifery passed from a female mystery, employing traditional medicines and superstitions, to a scientifically-based clinical skill, with both gains and losses to the patient. The case-mortality was high enough to make the increasing involvement of male surgeons socially acceptable, despite sexual taboos. Thus, as scientific knowledge of anatomy and physiology developed and was applied in the form of new techniques, so the midwives, who had less opportunity and inclination to acquire the new knowledge and skills, lost esteem and by the mid-eighteenth century were increasingly relegated to the service of the poor. The book also examines ideas about sexuality, menstruation, conception, pregnancy and lactation and shows how the views of society about femaleness, marital relations and the management of pregnancy and childbearing were influenced by these notions.
Preface Acknowledgements 1. English Obstetrical Textbooks Before 1740 2. The Legacy of the Ancients, and William Harvey 3. The Legacy of the Ancients, and the Anatomists 4. The Female Reproductive System 5. Sexuality and Conception 6. Development and Birth of the Foetus 7. Diagnosis of Pregnancy and Ante-natal Regimen 8. Pregnancy Prevention and Promotion 9. Gynaecology 10. Normal Childbirth 11. The Management of Obstetric Complications 12. The Manuall Practize Operative Delivery 13. Two Centuries of Obstetric Change Reviewed Appendix: Maternal Mortality: Some Notes on the Willughby Cases Notes Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: Birth; Birth of the Foetus; Childbirth; Conception; Contraception; Death in Childbirth; English Obstetrical Textbooks; English Obstetrics; Female Reproductive System; Foetal Development; Foetus; Getting Pregnant; Gynaecology; Maternal Mortality; Normal Childbirth; Obstetrics; Obstetric Complications; Operative Delivery; Pregnancy; Pregnancy Prevention; Pregnancy Promotion; Sexuality; Tudors; Tudor Contraception; Tudor Gynaecology; Tudor Medicine; Tudor Obstectrics; Tudor Period; Two Centuries of Obstetrics; William Harvey; Obstetrics -- England -- History; Gynecology -- England -- History; Medicine -- England -- History -- 16th century; Medicine -- England -- History -- 17th century; Electronic books